Implementation of Priority Measures to Eliminate the Accumulated Environmental Damage Caused by Chemical Enterprises in the City of Usolye-Sibirskoye, Irkutsk Region - S. A. Maltsev; E. V. Veber; V. A. Inozemtsev; M. V. Tsapok; P. Y. Belyakov; V. A. Kovtun; A. A. Antokhin (Вестник войск РХБ защиты, 2023)
A difficult situation, close to an environmental disaster, had been developing in the town of UsolyeSibirskoye, Irkutsk Region, since the 90s of the ХХ century. In 2020, the problem of accumulated environmental damage caused by chemical enterprises of the ecological zone of Lake Baikal, reached the federal level. On July 30, 2020, the President of the Russian Federation set the task of eliminating chemical contamination on the territory of the former enterprise LLC «Usoliekhimprom». The aim of this work is to summarize the experience of the Russian NBC Protection Troops, accumulated in course of eliminating the environmental damage, caused by the activities of chemical enterprises in the city of Usolye-Sibirskoye, Irkutsk region. The plan on priority measures was drawn up on the basis of careful monitoring of the «Usoliekhimprom» LLC industrial site in order to eliminate the chemical threats, existed at the facility. The special group of troops (forces) was formed to take part in liquidation activities. This group was formed from NBC Protection Troops, the State Atomic Energy Corporation «Rosatom», the Russian Emergencies Ministry, the Russian Guard and the Federal Biomedical Agency. In course of the training, the special group of troops (forces) worked out all the issues related to the safe conduct of the work, organized interaction between departments, and distributed the functional responsibilities. After the completion of the preparatory stage, the group began to work. 17 emergency railway tanks containing 104, 3 tons of toxic chemicals were fragmented, the above-ground part of the mercury electrolysis workshop with more than 600 tons of mercury was dismantled, the most dangerous wells Р-2Х and Р-5 with 107 thousand liters of epichlorohydrin production wastes were pumped out. In course of work, the detachment of the NBC Protection Troops carried out continuous monitoring of the chemical situation on the territory of the industrial site of «Usoliekhimprom LLC» and the adjacent territory. When carrying out liquidation measures, the personnel of the detachment of the NBC Protection Troops faced a number of problematic issues related to ensuring chemical safety. The solution of these problems made it possible to complete all the work in time and at a high professional level. All the work was carried out from August 8 to November 24, 2020.